مقارنة عيار ASLO المصل مع زرع المسحات الخارجية والداخلية للوزتين في قرار استئصال اللوزتين - خميس, عطية; المحمود, إياد; سليمان, علي (Latakia University Journal -Medical Sciences Series, 2018)
The high serum concentration of (ASLO) does not confirm sepsis in Streptococcus pyogenes, and therefore should not be the primary criterion for the tonsillectomy. In this study, we assess the feasibility of the palate tonsillectomy in cases where the level of Streptolysine O antibodies in the serum is high, then a bacterial culture of the two palate tonsils (bacterial culture of the outer surface and the inside of the tonsil), is performed to compare the high serum values of Streptolysine O, and to show the results of the internal and external swabs of the two tonsils. The study included 50 children (32 males and 18 females) between 5 and 15 years old, who have visited the ENT department at Al Assad University Hospital in Lattakia due to frequent tonsillitis (more than 3 times per year), who were scheduled for the surgical tonsillectomy. Before operation, each patient underwent a smear of the pharynx and the outer surface of the tonsils through the mouth using sterile cotton swabs. After the surgical tonsillectomy, the tonsils were placed in sterile containers and transferred to the laboratory at Al-Assad University Hospital, in addition to the calibration of the serum values of Streptolysine O antibodies. We found the following results:Out of 50 patients covered by the study, we had 40 patients with high serum values of Streptolysine O antibodies (i.e. 80%)Out of 40 patients with a high concentration of Streptolysine O antibodies, the results of the internal smears were positive for only 7 patients (17.5%).Out of 10 patients with normal values of Streptolysine O antibodies, the results of the internal and external smears were positive for only one patient (10%).For the external smears, the results were as follows: Out of 40 patients with a high concentration of Streptolysine O antibodies, the results of the external smears were positive for only six patients (15%).Out of the 10 patients with normal values of Streptolysine O antibodies, the results of external smears were all negative .We conclude from the previous study that the serum concentration values of the Streptolizine O antibodies cannot be a sufficient and only criterion for the decision of the tonsillectomy, and there should be more qualitative tests such as internal and external swabs. التركيز المصلي المرتفع من أضداد الستربتولايزين O (ASLO) لا يؤكد الإنتان بالعقديات المقيحة وبالتالي لا يجب أن يكون المعيار الأساسي في استئصال اللوزتين. نقيم في هذه الدراسة جدوى استئصال اللوزتين الحنكيتين في الحالات التي يكون فيها عيار أضداد الستربتولايزين O في المصل مرتفعة ومن ثم يتم إجراء الزرع الجرثومي للوزتين الحنكيتين( زرع جرثومي للسطح الخارجي وداخل اللوزة), من أجل إجراء مقارنة بين القيم المصلية المرتفعة لأضداد الستربتولايزين O وبين نتائج زرع المسحات الداخلية والخارجية للوزتين. شملت الدراسة 50 مريضا"(32 ذكور و18 إناث) من الأطفال (5-15عاما") المراجعين لقسم الأنف والأذن والحنجرة في مشفى الأسد الجامعي في مدينة اللاذقية بشكوى التهاب اللوزتين المتكرر (أكثر من 3 مرات خلال السنة الواحدة) والمقرر لهم استئصال اللوزتين جراحيا". أجريت لكل مريض قبل العمل الجراحي مسحة للبلعوم والسطح الخارجي للوزتين عبر الفم باستخدام ماسحات قطنية عقيمة. وبعد خضوع المرضى لاستئصال اللوزتين جراحيا" وضعت اللوزتين في عبوات عقيمة ونقلت إلى قسم الطب المخبري في مشفى الأسد الجامعي, بالإضافة لعيار القيم المصلية لأضداد الستربتولايزين O. كانت النتائج على النحو التالي, من أصل 50 مريض مشمولين بالدراسة كان لدينا 40 مريض لديهم ارتفاع في القيم المصلية لأضداد الستربتولايزين O أي بنسبة 80% , من أصل 40 مريض لديهم تركيز مرتفع من أضداد الستربتولايزينO , كانت نتائج زرع المسحات الداخلية إيجابية لـ(7) مرضى فقط بنسبة 17,5%. من أصل 10 مرضى لديهم قيم طبيعية من أضداد الستربتولايزين O, كانت نتائج زرع المسحات الداخلية إيجابية لمريض واحد فقط بنسبة 10%. وبالنسبة للمسحات الخارجية كانت النتائج على النحو التالي: من أصل 40 مريض لديهم تركيز مرتفع من أضداد الستربتولايزينO , كانت نتائج زرع المسحات الخارجية إيجابية لـ(6) مرضى فقط بنسبة 15%. من أصل 10 مرضى لديهم قيم طبيعية من أضداد الستربتولايزين O, كانت نتائج زرع المسحات الخارجية جميعها سلبية . كاستنتاجات من الدراسة السابقة وجدنا أن عيار القيم المصلية لأضداد الستربتولايزين O لا يمكن أن تكون معيار كاف ووحيد لاتخاذ القرار باستئصال اللوزتين ويجب أن يكون هناك اختبارات أخرى أكثر نوعية كالمسحات الداخلية والخارجية للوزتين.